A divulgação e recepção dos conceitos teóricos de Reuven Feuerstein e suas contribuições para a Psicologia e a Educação brasileiras. - Tatiana Campos Vasconcelos (2022)
This research aims to investigate the circulation, reception and appropriation of the theoretical concepts of the Theory of Structural Cognitive Modifiability, the Mediated Learning Experience and the Instrumental Enrichment Program, developed by Israeli psychologist born in Romania Reuven Feuerstein (19212014), in the scientific ideology of Brazilian psychology and education. Starting from the premise that human cognitive abilities can be modified through interpersonal dynamics, Feuerstein dedicated himself to promoting the cognitive and socioemotional development of people with cultural deprivation and learning difficulties. His theoretical proposals have been successfully applied in several countries. The investigation is based on a systematic review of the literature of a quantitative and qualitative nature, under a metaanalysis of the data regarding the circulation and implications of the concepts used in Brazil, in order to analyze what have been the results reported in the literature, what rereadings and transformations in the concepts and original procedures of the author that have been built in the Brazilian context. The assumption is that scientific theories, when circulating in different contexts, undergo appropriation processes that can result in innovations and in the elaboration of new research directions. The studies in question that use the theory, concepts and pedagogical procedures proposed by Feuerstein, especially the Theory of Structural Cognitive Modifiability, the criteria that define the Mediated Learning Experience and the Instrumental Enrichment Program, designed by the author. From a broad search in the Google Scholar and CAPES Periodicals databases, 199 studies were found published in Brazil between 1994 and 2021, with 98 articles, 17 Doctoral theses, 38 Master's dissertations, 46 works from various publications. Feuerstein's main concepts used in the publications are those related to the application of the Mediated Learning Experience (MLE), the theoretical foundation of pedagogical practices, the Theory of Structural Cognitive Modifiability and the use of the Instrumental Enrichment Program. As evidence of the effective application and growth of interfaces of his theories in communication with Brazilian studies, 14 areas of research were identified in which the presence of his theoretical proposals was observed. The qualitative analysis of the 77 published studies show: 1) the theory of the Mediated Learning Experience was the most present in the published studies, in broad communication with the educational areas covered, in a relevant and innovative way in the field of teaching technologies and teacher training, with emphasis on 2) the expansion of the conditions of Cognitive Modifiable, 3) the dialogue with a diversity of research areas, denoting the permeability of his work 4) positive and collaborative results in the interfaces found and 5) universal character of reception of his theories. This study reaches a territorial scope and breadth of educational fields that recognize the relevance and effectiveness of the application of Feuerstein's instruments and theories, in the improvement of learning, in addition to providing opportunities to interrelate their proposals to innovation on the act of teaching and learn.